Is Complex Music Socially Significant? Doing Ethnomusicology in South Asia - Burckhardt Qureshi, Regula (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1995)
In this article, four cases of ethnomusicological research on South Asian music are presented to substantiate the social essentiality (Wesentlichkeit) of music, and therefore the complementary role of a socially-grounded approach to studying complex musical traditions. Historiographically, it is argued that this social orientation progresses logically from, and is in keeping with, the growing cosmopolitan reality of musical scholarship and of music itself. Ethnomusicology draws resourcefully from its rich, inter-disciplinary heritage of musicology, music theory, anthropology, and area studies to yield tools of musical description and analysis that are culturally appropriate, culture-specific and yet cross-cultural, this paving a foundation for a truly comparative—and "Adlerian"— musicology.